Stability of geosynthetic reinforced embankments over stone column‐improved soft soil - Mohamed Labed; Mekki Mellas (Journal of Applied Engineering Science and Technology, 2016)
The stability of embankments on soft soils is a common problem; the reinforcement ofthis type of soil by a geosynthetic sheet above stone columns is a recent technique, for anexcellent distribution of the vertical stresses on the stone columns and the soft soils. This paperfocuses on the numerical analysis of a geosynthetic‐reinforced embankment over stone column‐improved soft soil. The finite difference code Fast Lagrangian Analysis of Continua in 3 Dimensions(FLAC3D) was used to determine the optimal placement of the geosynthetic sheet. Theembankment fill, the subsoil, and the stone columns were modeled by an elasto‐plastic model witha Mohr‐Coulomb yield criterion and associated flow rule. In this study, several geometrical andmechanical parameters have been considered, such as the stiffness modulus, the placement ofgeosynthetic sheet, and the internal friction angle of the embankment fill. The factor of safetyobtained by 3D numerical method was compared with those obtained by 2D numerical methods.The results of this study show the effect of the placement and stiffness of the geosynthetic sheeton the factor of safety.